Penggunaan Preposisi Dalam Paragraf Narasi Siswa Kelas X-1 SMA PGRI 2 Bandung - Zulfatun Anisah (Al Hikmah: Jurnal Studi Keislaman, 2019)
Abstract, the article, entitled "the use of Prepositions in the Narrative paragraph of Grade X-1 SMA PGRI 2 Bandung school year 2010/2011" examines four types of prepositions, such as preosisi the singular form of the word basic and noun, preposition forms compounds side by side and compounds are correlated. Methods this study used a qualitative descriptive. The results showed that in the singular form of the word preposition basics are just some of the students who can use prepositions in accordance with the rules. On the prepositions of the singular form of the word derivative not found one datapun that uses the preposition. On a compound preposition is attached also none of the data found. On a compound preposition correlates of students can use in accordance with the rules Keywords: basic word preposition, noun, plural side by side, and the compounds are correlated